2017
DOI: 10.18632/oncotarget.22470
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of quantitative ctDNA levels in non small cell lung cancer patients

Abstract: BackgroundCirculating tumor DNA (ctDNA) levels correlate well with tumor bulk. In this paper we aim to estimate the prognostic value of the dynamic quantification of ctDNA levels.Materials and MethodsA total of 251 serial plasma samples from 41 non-small-cell lung cancer patients who carried an activating EGFR mutation were analysed by digital PCR. For survival analysis, ctDNA levels were computed as a time-dependent covariate.ResultsDynamic ctDNA measurements had prognostic significance (hazard ratio for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…patients who carried driver mutations showed longer OS and PFS. Several studies have reported the use of NGS to detect the oncogenic driver mutations could guide therapy decisions and thus prolong the survival of NSCLC patients [16,17]. We believe that our real-world data may add new evidence for it.…”
Section: Discussionmentioning
confidence: 70%
“…patients who carried driver mutations showed longer OS and PFS. Several studies have reported the use of NGS to detect the oncogenic driver mutations could guide therapy decisions and thus prolong the survival of NSCLC patients [16,17]. We believe that our real-world data may add new evidence for it.…”
Section: Discussionmentioning
confidence: 70%
“…Resistance mutations to ALK-inhibitors can also be detected on ctDNA: in a cohort of 31 patients, McCoach et al showed that 16 samples (53%) contained 1–3 ALK resistance mutations [ 109 ]. ctDNA could, in the future, have wider clinical application as a prognostic marker and a marker of response to treatment independent of treatment type [ 110 ]. A recent study on 177 NSCLC highlighted that high ctDNA concentration was and independent prognostic factor for progression-free survival and overall survival.…”
Section: 1-lung Cancer Molecular Screenings Update On Validated Mmentioning
confidence: 99%
“…cfDNA profiling has proved to be useful to guide personalized treatments based on the molecular profile, for early detection of resistance mechanisms [35,36], early detection of disease recurrences, as well as tumor response to therapy monitoring [37] by means of sequential liquid biopsies. Furthermore, several studies comparing the detection of EML4-ALK translocation by formalin-fixed paraffinembedded (FFPE) tissuesand liquidbiopsy havereportedthat indeed cfDNA can be used as a surrogate of FFPE DNA [38].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…The sensitivity and specificity for the detection of EML4-ALK rearrangements in RNA isolated from platelets in patients has been reported to be between 65% and 100% respectively [56]. Even with the optimization of the preanalytical conditions of liquid biopsy samples, the sensitivity of the detection of EML4-ALK rearrangements using cfRNA was lower compared to platelet RNA (21% and 65% respectively) [36].…”
Section: Tumor-educated Platelets (Teps)mentioning
confidence: 99%